Anaximander’s Treatise on the Earth - Rossetti, Livio (Peitho. Examina Antiqua, 2013)
The present paper argues that the teachings of Anaximander are much better knowable than they actually appear, since a number of his teachings have the privilege of being almost transparent in their predicative content as well as in their logic. As a matter of fact, one can quite easily come to understand the train of thought which lies behind Anaximander’s most momentous conjectures. Thus, a largely unexpected Anaximander comes to light despite the availability of the majority of the relevant sources since 1903. Two main areas appear to be particularly prominent: on the one hand, the complex body of various conjectures and doctrines that helps to understand the system of spatial relationships from Miletus to the stars and, on the other hand, the equally complex body of conjectures and doctrines whose primarily concern is the macro-story of the Earth from its most remote past to its predictable future. The merits of Anaximander as an earth-researcher are much greater than one could actually imagine. It is suggested here that what philosophy owes to him in particular lies in his quest for knowledge, his method, his cognitive hybris, and his intellectual discipline, rather than individual doctrines. A comparison with Thales follows in the last paragraph.